GABAA receptor plasticity in Jurkat T cells - Dionisio, Leonardo Raul (2013)
GABAA receptors (GABAAR) mediate inhibitory neurotransmission in the human brain. Neurons modify subunit expression, cellular distribution and function of GABAAR in response to different stimuli, a process named plasticity. Human lymphocytes have a functional neuronal-like GABAergic system with GABAAR acting as inhibitors of proliferation. We here explore if receptor plasticity occurs in lymphocytes. To this end, we analyzed human T lymphocyte Jurkat cells exposed to different physiological stimuli shown to mediate plasticity in neurons: GABA, progesterone and insulin. The exposure to 100 μM GABA differently affected the expression of GABAAR subunits measured at both the mRNA and protein level, showing an increase of α1, β3, and γ2 subunits but no changes in δ subunit. Exposure of Jurkat cells to different stimuli produced different changes in subunit expression: 0.1 μM progesterone decreased δ and 0.5 μM insulin increased β3 subunits. To identify the mechanisms underlying plasticity, we evaluated the Akt pathway, which is involved in the phosphorylation of β subunits and receptor translocation to the membrane. A significant increase of phosphorylated Akt and on the expression of β3 subunit in membrane occurred in cells exposed 15 h to GABA. To determine if plastic changes are translated into functional changes, we performed whole cell recordings. After 15 h GABA-exposure, a significantly higher percentage of cells responded to GABA application when compared to 0 and 40 h exposure, thus indicating that the detected plastic changes may have a role in GABA-modulated lymphocyte function. Our results reveal that lymphocyte GABAAR are modified by different stimuli similarly and by similar mechanisms to those in neurons. This property is of significance for the development of future therapies involving pharmacological modulation of the immune response.